Program Makan Bergizi Gratis (MBG) sebagai Hidden Curriculum dalam Pembentukan Karakter Siswa Perspektif Pendidikan Islam - Sulviana Intan Maharani; Najmi Faza (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The Free Nutritious Meal Program (MBG) is a government policy aimed at improving the nutritional quality of students as part of human resource development. However, this program not only impacts health but also has educational dimensions that can shape students’ personalities through a habit-forming process. This article aims to analyze the Free Nutritious Meal Program (MBG) as a form of hidden curriculum from an Islamic learning perspective. This research uses a qualitative approach with library research methods through analysis of scientific literature, government policies, and Islamic learning concepts related to character building. The results show that the implementation of the MBG incorporates Islamic learning values such as discipline, responsibility, healthy living, simplicity, gratitude, and togetherness, which are internalized through students’ daily activities. These values emerge as a form of hidden curriculum because they are not formally taught in the curriculum but are created through application and habituation throughout the program. From an Islamic education perspective, habituation is a crucial part of shaping students’ morals and character. Therefore, the MBG Program can be understood not only as a nutritional fulfillment policy but also as a medium for character education based on Islamic values. This research confirms that social policy in the field of education has the ability to become an instrument for character formation through an indirect educational process.